Pentazocine-induced contractures: Dilemma in management - Kumar, Dileep (Indian J Pharmacol, 2015)
Pentazocine is a commonly used synthetic opioid analgesic for moderate to severe pain secondary to various conditions. Complications of parenteral opioid abuse including localized ulcerations, abscess, indurations, and sclerosis are well-documented. We present a rare case of drug abuse due to pentazocine (Fortwin) in a 32-year-old female, who had severe myogenic contractures of her knee joints.